New organic 4-(4-methoxystyryl)-1-methylpyridinium crystals for nonlinear optical applications - Lee, Yun Sang; Yoon, Woojin; Yun, Hoseop; Jazbinsek, Mojca; Yu, In Cheol; Rotermund, Fabian; Kim, Dongwook; Kwon, O. Pil (Bulletin of the Korean Chemical Society, 2022)
In this study, an organic nonlinear optical salt crystal, 4-(4-methoxystyryl)-1-methylpyridinium 4-bromobenzenesulfonate (MOS-BBS), is newly reported. MOS-BBS crystals exhibit perfectly parallel molecular ordering of 4-(4-methoxystyryl)-1-methylpyridinium (MOS) cationic chromophores with noncentrosymmetric P1 space group symmetry, which provides an optimal configuration for maximizing the macroscopic second-order optical nonlinearity. The macroscopic optical nonlinearity of the MOS-BBS crystals is very large, with the diagonal effective first hyperpolarizability of 160 × 10−30 esu. Furthermore, the MOS-BBS crystals exhibit a high thermal crystal-phase stability. The lowest phase transition temperature of the MOS-BBS crystals is 265°C, which is ~90°C higher than that of previously reported MOS-based crystals.
Keywords: Cationics; First hyperpolarizabilities; Molecular ordering; Non-linear optical; Nonlinear optical applications; Organic crystal; Organics; Salt crystals; Second order optical nonlinearity; Space-group symmetry; first hyperpolarizability; nonlinear optics; organic crystals